2014
DOI: 10.1002/2013jc009558
|View full text |Cite
|
Sign up to set email alerts
|

Caspian Sea surface circulation variability inferred from satellite altimeter and sea surface temperature

Abstract: Multiyear (1993Multiyear ( -2007 satellite-derived Sea Level Anomaly (SLA), Sea Surface Temperature (SST), and model-derived mean dynamic topography were used together to analyze climatological and interannual variations of the Caspian Sea surface circulation. Constructed geostrophic currents are in good agreement with the known circulation features of the Caspian Sea, obtained from models and verified by some drifter observations. It is shown that the climatological surface circulation of the Middle Caspian S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…From satellite-derived products, Gunduz (2014) provided a description of geostrophic currents and highlighted the strong interannual variability of the Caspian Sea circulation. The CCS is dominated by a cyclonic gyre in the winter which briefly switches to an anti-cyclonic circulation during summer while the SCS exhibits a dipole pattern (anticyclonic in the north and cyclonic further south).…”
Section: Introductionmentioning
confidence: 99%
“…From satellite-derived products, Gunduz (2014) provided a description of geostrophic currents and highlighted the strong interannual variability of the Caspian Sea circulation. The CCS is dominated by a cyclonic gyre in the winter which briefly switches to an anti-cyclonic circulation during summer while the SCS exhibits a dipole pattern (anticyclonic in the north and cyclonic further south).…”
Section: Introductionmentioning
confidence: 99%
“…The currents are primarily wind-generated. Horizontal dynamics is characterized by predominating cyclonic circulation at the sea center and by generation of separate local eddies [29].…”
mentioning
confidence: 99%
“…During the winter, wind blows to the west, and in summer the wind direction changes dramatically and the wind starts to blow to the south. Gunduz (2014) has shown that variation of the wind speed and direction (Fig. 5 in the paper) may have an influence on the changing of the cyclonic circulation in winter to the anticyclonic one in summer in the MCS.…”
Section: Seasonal Circulationmentioning
confidence: 84%